The Economics of Property Rights in Early and Medieval Christianity. (February 2017) - Koehler, Benedikt
Abstract: Early and medieval Christianity pioneered an economics of property rights that had no precedent in antiquity. The early Church Fathers Tertullian, Ambrose, and John Chrysostomos successively evolved conceptions of the right to own property as a prerequisite for poor relief, and the basis of the right to own property was later formulated by Pope John XXII to settle a dispute on this issue instigated by Francis of Assisi. This article challenges assessments advanced by Joseph Schumpeter, Jacob Viner, and Frank Knight, who argued that the doctrines of Christianity were devoid of economics, and draws attention to the work of Georg Ratzinger (1844–1899), who first expounded how in early Christianity property rights and poor relief were linked.